Palliation and breast cancer. Issue 5 (18th January 2017) - Yip, Cheng‐Har
Abstract : Metastatic breast cancer is an incurable disease. With improvement in systemic therapy, survival has improved over the past few years. Removing the primary tumor has shown improved survival in retrospective studies, but this may be due to selection bias. The first reported randomized controlled trial (RCT) from India showed no difference in survival with surgery. However another RCT from Turkey showed that a select group of patient with bone‐only metastases have a survival benefit.